PERBEDAAN KEJADIAN DEPRESI PADA PASIEN CHRONIC KIDNEY DISEASE ON HEMODIALISIS YANG DIPENGARUHI DUKUNGAN KELUARGA - Yuliana Tina Mutiara; Wahyu Hidayati; ahmad asyrofi (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
EFFECT OF APPLICATION OF GENERALIST NURSING ACTION: ANSIETAS ON CHRONIC POSTED DISEASE PATIENTS ABSTRACTUnhealthy lifestyle caused of chronic kidney disease. Urban communities are particularly vulnerable to unhealthy lifestyles, which can lead to chronic kidney disease. Chronic kidney disease is a condition which the kidney are permanently damaged and ultimately have an impact to the function of the kidney. Physical changes that occur in patients with chronic kidney disease associated with signs and symptom’s the severity of the disease. It will certainly affect the psychosocial condition of patients. Psychosocial problems that arise in hopitalized patients with chronic kidney is anxiety. This Scientific works aims to describe the nursing care of anxiety in patients with Chronic Kidney disease especially with relaxation techniques. Patients who are able to overcome their anxiety will improve the effectiveness of the physical treatments that are being undertaken. Thus, the nurse's role in providing psychosocial nursing care is necessary so that anxiety problems do not cause adverse impact to the patient. Keywords: Axiety, Chronic Kidney Disease, Relaxation technique